2004
DOI: 10.1038/sj.bjc.6601526
|View full text |Cite
|
Sign up to set email alerts
|

A randomised phase II study of weekly paclitaxel or vinorelbine in combination with cisplatin against inoperable non-small-cell lung cancer previously untreated

Abstract: Phase II studies have suggested that weekly paclitaxel has a higher response rate and better toxicity profile than the conventional schedule of once every 3 or 4 weeks. Our aim was to evaluate the efficacy of weekly paclitaxel plus cisplatin (PC) vs vinorelbine plus cisplatin (VC) in chemonaïve non-small-cell lung cancer (NSCLC) patients. From October 2000 to May 2002, 140 patients were enrolled. The treatment dose was P 66 mg m À2 intravenous infusion (i.v.) on days 1, 8, and 15, and C 60 mg m À2 i.v. on day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(58 citation statements)
references
References 18 publications
(34 reference statements)
1
54
2
Order By: Relevance
“…24 In contrast, the current results indicated that gefitinibbased treatment produced no change in symptom scores after 2 months of treatment, indicating that there was better effective prolongation of symptom deterioration.…”
Section: Discussioncontrasting
confidence: 54%
“…24 In contrast, the current results indicated that gefitinibbased treatment produced no change in symptom scores after 2 months of treatment, indicating that there was better effective prolongation of symptom deterioration.…”
Section: Discussioncontrasting
confidence: 54%
“…The schedule was vinorelbine 23 mg/m 2 IV on days 1, 8, and 15 plus cisplatin 60 mg/m 2 on day 1 of every 4 weeks [21]. The vinorelbine dose intensity was slightly lower, while the cisplatin dose intensity was higher in the present study.…”
Section: Discussionmentioning
confidence: 52%
“…Between 2003 and 2004, the activity/toxicity of weekly paclitaxel combined with cisplatin has been reported in three consecutive studies [27][28][29].…”
Section: Time To Treatment Failure and Survivalmentioning
confidence: 99%
“…A few weeks later, a phase III study comparing weekly paclitaxel plus cisplatin vs. vinorelbine plus cisplatin in 140 chemo-naïve NSCLC patients was reported [28]. The treatment dose [28] was paclitaxel 66 mg/m 2 on days 1, 8, and 15, and cisplatin 60 mg/m 2 on day 15, or vinorelbine 23 mg/ m 2 on days 1, 8, and 15, and cisplatin 60 mg/m 2 on day 15, every 4 weeks.…”
Section: Time To Treatment Failure and Survivalmentioning
confidence: 99%
See 1 more Smart Citation